Intestinal obstruction due to a rare tumor in the meckel's diverticulum in a 10-month-old boy - Gulan Maree; Mohammad Nasser (Elsevier, 2022)
Meckel's diverticulum is the most common congenital abnormality of the gastrointestinal tract. It can cause many complications, such as hemorrhage, intestinal obstruction, intussusception, perforation, and, very rarely, vesicodiverticular fistulae and tumors. Tumors in Meckel's diverticulum are extremely uncommon.These tumors can be benign or malignant. Lipoblastomas are rare benign mesenchymal tumors that arise from embryonic fat cells. Herein, we present the case of a 10-month-old patient with intestinal obstruction due to a benign tumor (lipoblastoma) in the Meckel diverticulum synchronous with volvulus.The tumor was excised completely. Histopathology of this lesion confirmed the lipoblastoma. To our knowledge, this is the first case of a lipomablastoma within a meckel diverticulum in a child that has been reported in English literature.